The double plate technique combined with the cable technique for treating sternoclavicular joint dislocation: a case report - Yinglong Xu; Jin Zhu; Li Huang; Caili Huang; Zonggui Huang; Hai Dai (BMC Musculoskeletal Disorders)
Abstract Background Sternoclavicular joint dislocation (SJD) is rare, and joint instability after dislocation easily leads to deformity, pain, and limitations in performing activities, often requiring surgical treatment. Currently, there is no ideal internal fixation method for SJD. Case presentation We report the case of a 38-year-old female patient with anterior dislocation of the right sternoclavicular joint (SJ) caused by a car accident who underwent open reduction and internal fixation using the double plate technique combined with the cable technique. Postoperative follow-up showed good mobility of the right shoulder joint, with a Rockwood SJ score of 15, and no complications such as loss of joint repositioning, localized pain, and vascular and nerve injuries. At the last follow-up at 6 months after surgery, the wire was found to be broken without displaced, and the internal fixation was removed. Conclusion The double plate technique combined with the cable technique may be an effective treatment option for SJD, and 1.2 mm titanium cables may be more advantageous for cable fixation.